Rancang Bangun Smart Alert - Dedi Mulyono; Gilang M Rahmadi; Riko Saputra; Yuvani Oksarianti; Ahmad Arif (Universitas Negeri Padang, 2021)
Abstract Motorcycles are the biggest contributor to driving accidents in Indonesia. Some of the accidents that occurred were caused by the negligence of passengers who did not pay attention to the clothes worn when riding a motorcycle. Smart Alert is an innovation designed as an effort to prevent the passenger's skirt or hijab from being wrapped around a motorcycle chain or spokes. This tool utilizes several simple electronic components such as batteries, sensor, microcontroller, buzzer and LED as a circuit. This distance detecting device is fully controlled by a microcontroller with an ultrasonic sensor to detect the distance on one side and its supporting components. With the Smart Alert, the potential for accidents can be avoided and minimized thereby reducing the number of driving accidents in Indonesia. Keywords Buzzer, Crash, LED, Microcontroller, Smart Alert Abstrak Sepeda motor merupakan penyumbang kecelakaan berkendara terbesar di Indonesia. Beberapa kecelakaan yang terjadi tersebut diakibatkan oleh kelalaian dari penumpang yang tidak memerhatikan pakaian yang dikenakan ketika akan menaiki sepeda motor. Smart Alert merupakan inovasi yang dirancang sebagai upaya pencegahan terlilitnya rok atau hijab penumpang pada rantai atau jari-jari sepeda motor. Alat ini memanfaatkan beberapa komponen elektronik sederhana seperti baterai, sensor, microcontroller, buzzer serta LED sebagai rangakaiannya. Alat yang mendeteksi jarak ini dikendalikan sepenuhnya oleh sebuah microcontroller dengan sebuah sensor ultrasonik untuk mendeteksi jarak pada suatu sisi beserta komponen-komponen penunjangnya. Dengan adanya Smart Alert maka potensi kecelakaan dapat dihindari dan diminimalisir sehingga menurunkan angka kecelakaan berkendara di Indonesia. Kata Kunci Buzzer, Kecelakaan, LED, Microcontroller, Smart Alert